2022
DOI: 10.3390/insects13070590
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Substrate on the Nutrient Content and Fatty Acid Composition of Edible Insects

Abstract: Demand for new food sources and production methods is increasing due to overall population growth, as well as the aim towards more sustainable use of natural resources and circular economy. Edible insects already used in many parts of the world have recently attracted interest as a new protein source in Europe, and novel food acceptance procedures are ongoing in the European Union for several insect species. In this paper, the effects of substate on the nutritional value, especially the fatty acid composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Moreover, eicosanoic acid was recorded highest in BM, but low and comparable in SC and GC (F = 18.32; df = 2; p = 0.00279). Our findings are in agreement with fatty acid spectra reported on other edible insects [ 36 , 38 , 39 , 40 ]. Notwithstanding the effect of insect species, studies have also shown that the fatty acid spectra of edible insects are partly dependent on the fatty acid composition of their feed [ 41 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, eicosanoic acid was recorded highest in BM, but low and comparable in SC and GC (F = 18.32; df = 2; p = 0.00279). Our findings are in agreement with fatty acid spectra reported on other edible insects [ 36 , 38 , 39 , 40 ]. Notwithstanding the effect of insect species, studies have also shown that the fatty acid spectra of edible insects are partly dependent on the fatty acid composition of their feed [ 41 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 93%
“…Edible insects are known as a valuable source of fatty acids, whose properties have been considered to be closer to plant than animal oils [ 31 , 36 , 37 , 38 , 39 , 40 ]. Ten free fatty acids were studied and were present in all three insects, though in varying concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…from A. domesticus and B. mori) may potentially be used in the substitution of soybean oil to improve the energy density of ruminant diets and to modulate ruminal biohydrogenation, increasing the concentration of the health-promoting vaccenic (C18:1 trans-11) and rumenic (C18:2 cis-9, trans-11) acids, without altering the concentrations of C18:1 trans-10 (which may exert potentially negative effects on animal performance and human health). However, the contribution that insects may provide to the overall quality and the nutraceutical value of milk, meat and derived products is expected to be quite variable, since the fatty acid profile of insects strongly depends on the insect species, the developmental stage, the applied technological processes, and the substrate used for insect rearing (Gasco et al, 2022;Riekkinen et al, 2022). Most insect meals tested so far for monogastric feeding purposes are characterised by a high content of unsaturated fatty acids (mainly of the n-6 series) and could therefore be interesting for the improvement of the quality of ruminantderived food products.…”
Section: Quantitative and Qualitative Aspects Of Animal Performancementioning
confidence: 99%
“…It has also been reported that mealworms do not only consume existing food supplies more effectively than other animals, but they can also quickly transform low-nutrient by-products of popular crops like maize, wheat, millet, and peanuts into high-quality food [9][10][11]. Some studies have also been conducted on the nutritional makeup of mealworms but it has been reported that values vary by species and developmental [12][13][14][15]. The yellow mealworm can be fed to animals in its live form, but more commonly they are dried and may be ground into powder.…”
Section: Introductionmentioning
confidence: 99%